2021
DOI: 10.2174/1573398x17666210129125703
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the Effect of Arbidol Plus Hydroxychloroquine vs Hydroxychloroquine Alone in Treatment of COVID-19 Disease: A Randomized Clinical Trial

Abstract: Background and aim: The main challenging issue about coronavirus disease 2019 (COVID-19) is the production of safe and stable vaccines, which is a very long process. Due to the emergency situation, regular and extensive screening of available and traditional drugs, which are commonly used for the treatment of similar viral diseases, can be a reasonable option. The present study aimed to compare the administration of hydroxychloroquine (HCQ) plus arbidol to the use of HCQ alone in the treatment of COVID-19 infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The study introduced Umifenovir as an effective treatment for moderate to severe patients, showing not only a reduced time of CRP (C-reactive protein) normalization, but also a decreased hospitalization stay and mortality compared with those reported for Hydroxychloroquine. 31 Conversely, another study has shown that additional Umifenovir was not effective in decreasing the duration of SARS-CoV-2 in severe patients and improving the prognosis in non-intensive care unit (non-ICU) patients and mortality. 32 A recent retrospective study concluded that Umifenovir did not provide a significant improvement in the treatment of COVID-19 for non-ICU patients and that randomized clinical trials should be performed.…”
Section: Remdesivirmentioning
confidence: 99%
“…The study introduced Umifenovir as an effective treatment for moderate to severe patients, showing not only a reduced time of CRP (C-reactive protein) normalization, but also a decreased hospitalization stay and mortality compared with those reported for Hydroxychloroquine. 31 Conversely, another study has shown that additional Umifenovir was not effective in decreasing the duration of SARS-CoV-2 in severe patients and improving the prognosis in non-intensive care unit (non-ICU) patients and mortality. 32 A recent retrospective study concluded that Umifenovir did not provide a significant improvement in the treatment of COVID-19 for non-ICU patients and that randomized clinical trials should be performed.…”
Section: Remdesivirmentioning
confidence: 99%
“…Following molecular dynamics simulations, umifenovir targets the virus by exhibiting a higher affinity than the angiotensin-converting enzyme 2 for the receptor-binding domain of the spike protein [ 72 , 73 ]. Because the drug is not approved by the FDA and is of limited access worldwide, the substance is poorly involved in large clinical trials and some contradictory results, obtained on small cohorts, have been reported [ 74 , 75 , 76 ].…”
Section: New Hopes?mentioning
confidence: 99%
“…The COVID-19 pandemic has led to an unprecedented volume of hospital visits and admissions, including those with suspected COVID-19, resulting in elevated levels of overcrowding in hospitals and healthcare centers. 1 , 10 , 11 This circumstance has contributed to a delay in care and poorer outcomes, such as increased morbidity and mortality, especially in emergency departments (EDs) where resources are limited. 3 , 12 , 13 Critically ill patients are particularly vulnerable to encountering these adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…We performed the study on a cohort of patients from Iran, a country with a high number of confirmed COVID-19 cases and related deaths. 3 , 6 , 11 , 13 , 30 …”
Section: Introductionmentioning
confidence: 99%